2012
DOI: 10.2308/ajpt-50374
|View full text |Cite
|
Sign up to set email alerts
|

When the PCAOB Talks, Who Listens? Evidence from Stakeholder Reaction to GAAP-Deficient PCAOB Inspection Reports of Small Auditors

Abstract: SUMMARY: Section 104 of the Sarbanes-Oxley Act (SOX) created the Public Company Accounting Oversight Board (PCAOB). The PCAOB conducts inspections of registered public accounting firms that provide audits for publicly traded companies. The results of the inspection process are summarized in publicly available reports at the PCAOB website. Using these reports, we categorize the inspection reports into three levels of increasing severity: clean, GAAS-deficient, and GAAP-deficient. We examine the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(61 citation statements)
references
References 29 publications
4
57
0
Order By: Relevance
“…In addition, the analysis shows that companies that dismissed audit firms with deficiencies were more likely to hire an audit firm with clean reports. 7 Abbott et al (2013) came to the same result. They examined the association between GAAP-deficient reports and changes in the number of clients.…”
Section: Recognition Of Pcaob Inspections For Decision-makingsupporting
confidence: 72%
See 2 more Smart Citations
“…In addition, the analysis shows that companies that dismissed audit firms with deficiencies were more likely to hire an audit firm with clean reports. 7 Abbott et al (2013) came to the same result. They examined the association between GAAP-deficient reports and changes in the number of clients.…”
Section: Recognition Of Pcaob Inspections For Decision-makingsupporting
confidence: 72%
“…Empirical work on the former peer review system has applied alternative evaluation methods to assess whether reviewed firms provide higher audit quality than non-reviewed firms (Deis & Giroux, 1992;Krishnan & Schauer, 2000;O'Keefe et al, 1994;Rollins & Bremser, 1997). In contrast, research on the PCAOB inspections has used audit client-specific measures to evaluate the extent to which inspection contributes to audit quality (Abbott, Gunny, & Zhang, 2013;Carcello et al, 2011;Gramling, Krishnan, & Zhang, 2011;Offermanns & Peek, 2011). Other studies have researched the effect of inspections on the composition of the audit market (DeFond & Lennox, 2011), or have directly asked financial experts about the effect of peer reviews and PCAOB inspections on audit quality Felix & Prawitt, 1993;McCabe, Luzi, & Brennan, 1993;Newman & Oliverio, 2010).…”
Section: Effect Of Peer Reviews and Inspections On Audit Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…(9) The firm's internal review and PCAOB inspection reports. Prior research (e.g., Gunny and Zhang 2013;Abbott, Gunny, and Zhang 2013) suggest that PCAOB inspection findings are negatively associated with audit quality. The AC should acknowledge its knowledge that a PCAOB inspection occurred on its audit, and comment on its findings (Q20)…”
Section: Auditor Competence (Expertise)mentioning
confidence: 99%
“…In addition, Tanyi and Litt (2016) show that small and midsize audit firms inspected annually are more selective in their choice of new clients in the post-inspection period compared to the triennially inspected firms. Furthermore, it has been shown that clients with effective audit committees or with high potential reporting quality of GAAP-deficient triennially inspected auditors are more likely to switch to audit firms without GAAP related deficiencies (Abbott et al 2013). Finally, the capital market also appears to react to the PCAOB inspection reports.…”
Section: Introductionmentioning
confidence: 99%